The emergence of family medicine in India-A qualitative descriptive study. - Archna Gupta; Ramakrishna Prasad; Sunil Abraham; Nisanth Menon Nedungalaparambil; Onil Bhattacharyya; Megan Landes; Sanjeev Sridharan; Carolyn Steele Gray (Public Library of Science (PLoS), 2023)
Countries globally are introducing family medicine to strengthen primary health care; however, for many, that process has been slow. Understanding the implementation of family medicine in a national context is complex but critical to uncovering what worked, the challenges faced, and how the process can be improved. This study explores how family medicine was implemented in India and how early cohort family physicians supported the field's emergence. In this qualitative descriptive study, we interviewed twenty family physicians who were among the first in India and recognized as pioneers. We used Rogers's Diffusion of Innovation Theory to describe and understand the roles of family physicians, as innovators and early adopters, in the process of implementation. Greenhalgh's Model of Diffusion in Service Organizations is applied to identify barriers and enablers to family medicine implementation. This research identifies multiple mechanisms by which pioneering family physicians supported the implementation of family medicine in India. They were innovators who developed the first family medicine training programs. They were early adopters willing to enter a new field and support spread as educators and mentors for future cohorts of family physicians. They were champions who developed professional organizations to bring together family physicians to learn from one another. They were advocates who pushed the medical community, governments, and policymakers to recognize family medicine's role in healthcare. Facilitators for implementation included the supportive environment of academic institutions and the development of family medicine professional organizations. Barriers to implementation included the lack of government support and awareness of the field by society, and tension with subspecialties. In India, the implementation of family medicine has primarily occurred through pioneering family physicians and supportive educational institutions. For family medicine to continue to grow and have the intended impacts on primary care, government and policymaker support are needed.